Thyroid Cancer The Road From Genes to Successful Treatment - Kostoglou-Athanassiou, Ifigenia (IntechOpen, 2023)
Thyroid cancer is the most common endocrine cancer, although it is relatively rare compared to other cancers. Standard treatment involves thyroidectomy and radioiodine administration followed by life-long thyroxine administration. However, until recently, there was no medical treatment for advanced thyroid cancer. Advances in the genetics of thyroid cancer and in the treatment of other forms of cancer with tyrosine kinase inhibitors have revolutionized the treatment of advanced thyroid cancer. This book provides a comprehensive overview of thyroid cancer. It is organized into two sections on genetics and treatment. Chapters address such topics as the genetic susceptibility to differentiated thyroid cancer, the molecular basis of radioiodine treatment in thyroid cancer, recent developments in the medical treatment of advanced thyroid cancer, systemic therapy in thyroid cancer, and much more.